Jekajeh: Dinamika Daya Juang Santriwati untuk Bertahan di Pondok Pesantren - Nada Shobah; S. Anis Al-Habsyi; Mohammad Mahpur; Yulia Sholichatun (Jurnal Psikologi Islam dan Budaya, 2023)
It is hoped that jekajeh, which is recognized and accommodated according to the social field of boarding students, can provide the benefit of a space for expression of female students that is in line with the hobbies and development of female students' psychological potential. This ethnographic qualitative research aims to discover the dynamics of jekajeh as a student's striving behavior, how to care for jekajeh, and how consultative stimulants are known to make jekajeh in Islamic boarding schools healthier. Participants were 5 female students at the Nurul Quran Kraksaan Islamic Boarding School aged 18-23 years. Data collection used in-depth interview techniques and open questionnaires, with inductive-abstractive data analysis. The results found that jekajeh is a form of problem solving, emotional control, and encouragement to pray. Hobbies became part of the potential solution to jekajeh, and the consultation space in interviews plays a role in breaking down pressure into striving power (jekajeh), which may or may not persist. This study has the implication that Islamic boarding schools need a response and provide psychological services for the growth of striving power (jekajeh), so that students remain healthy and survive in Islamic boarding schools.